Optimization of tool path parameter for machining of free form surface profile of pre harden steel - Siti Aishah, Arman (2016)
This project deal with the optimization of machining parameter of the free form design of pre harden steel along with the tool path strategy that classified as the hard-to-cut material. In this project, there are 2 main scope, they are tool path strategy that could machine the product to the uniformity result of the best surface roughness and low tool wear effect. The optimization machining parameter that need to be set up by specific analysis software. The tool path strategy generated in CAD CAM system in Catia software need to be study to produce the quality of product at the end of experiment and could improve the cutting tool life. In the other hand, research on the machining parameter in term of Feed Rate, Depth of Cut and Width of Cut need to be developed to find the most optimize parameter that will produce best surface finish and tool wear rate. Thus in the optimization of machining parameter, Taguchi method with 2 level and 3 factor of